2017
DOI: 10.15625/0866-7160/v39n3.9243
|View full text |Cite
|
Sign up to set email alerts
|

Butterflies (Lepidoptera - Rhopalocera) of coastal areas of Southern West Bengal, India

Abstract: The present study was carried out to prepare a checklist of butterflies in the Coastal areas of Purba Medinipur District of southern West Bengal between January 2014 and February 2016. A total of 112 butterfly species belonging to 74 genera under 14 subfamilies and five families were recorded during the study period. Nymphalidae and Lycaenidae were the most dominant family, whereas Papilionidae was the least dominant family. Among 112 butterfly species recorded, 9 species were legally protected under the Wildl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Limited studies have been carried out on butterfly fauna in the undivided Midnapore District, and previous records from the region include the report of 112 species from the coastal area of Purba Medinipur (Payra et al 2017) and 82 species from Midnapore Municipality area of West Midnapore District (Biswas et al 2019) and remaining part was untouched. The present study aims to document butterflies in the undivided Midnapore district and prepare a checklist along with habitat ecology and management status for undertaking proper conservation action in near future.…”
Section: Platinum Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited studies have been carried out on butterfly fauna in the undivided Midnapore District, and previous records from the region include the report of 112 species from the coastal area of Purba Medinipur (Payra et al 2017) and 82 species from Midnapore Municipality area of West Midnapore District (Biswas et al 2019) and remaining part was untouched. The present study aims to document butterflies in the undivided Midnapore district and prepare a checklist along with habitat ecology and management status for undertaking proper conservation action in near future.…”
Section: Platinum Open Accessmentioning
confidence: 99%
“…Status of the butterfly was categorized under five categories: rare (R), not rare (NR), not common (NC), common (C), and very common (C). Butterflies having <20 % sightings were marked as rare butterflies, 20-40 % not rare, 40-60 % not common, 60-80 % common, and >80% very common (Payra et al 2017;Samanta et al 2017).…”
Section: Data Collectionmentioning
confidence: 99%
“…Mukherjee et al found 54 species in Kolkata metropolis [29] . Payra et al reported 112 butterfly species from the costal belt of Purba Medinipur [30] . Mandal et al enlightened up about 70 species from the Rice Research Station and adjoining locality in Chinsurah, Hooghly [31] .…”
Section: Resultsmentioning
confidence: 99%
“…Butterfly research in West Bengal is nearly contemporary with India, different analysts at various occasions propelling butterfly study of the southern division of this state [25,26,27,28,29,30,31]. Major research on butterflies found from Purba Medinipur among three districts of study area [32,33,34]. A unique field study from Paschim Medinipur district point outs that 82 species of butterflies present in the urban area of Midnapore [7].…”
Section: Introductionmentioning
confidence: 99%
“…At present, this study has found 125 species from the entire Paschim Medinipur District. The most research on butterfly documentation has been from the Purba Medinipur district[32,33,34]. The primary documentation finished from the ContaiDiversity of Butterflies (Lepidoptera: Rhopalocera) of Jhargram, Paschim and Purba Medinipur Districts, West Bengal, India (Kanthi) region, then the major research was done from the entire coastal area of this district and afterwards from the Haldia industrial zone.…”
mentioning
confidence: 99%